1998
DOI: 10.1038/sj.ejcn.1600516
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in Chinese elderly female vegetarians, vegans, lacto-vegetarians and omnivores

Abstract: Objectives: To compare the bone mineral density and dietary intake of elderly Chinese vegetarian women with omnivores, to compare the bone mineral density of Chinese`vegans' and`lactovegetarians', and to study the relationship between nutrient intake and BMD in vegetarians. Design: A cross-sectional survey. Setting and subjects: A community-based study. The vegetarian women (aged 70±89 y) (n 76) were noninstitutionalized subjects. All of them were Buddhists. Their bone mineral density were compared to normal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 26 publications
5
50
2
2
Order By: Relevance
“…Three studies have reported lower bone mineral density or bone mineral content in vegans compared with omnivores or other vegetarians (Chiu et al, 1997;Parsons et al, 1997;Outila et al, 2000). Another study found no difference in bone mineral density between vegans and lacto-vegetarians, although the researchers noted a positive correlation between calcium intake and bone mineral density (Lau et al, 1998). A small, short-term intervention study found that calcium balance remained positive after 10 days consuming a vegan diet as well as after 10 days consuming a lacto-vegetarian diet, despite a significantly lower mean calcium intake on the vegan diet (Kohlenberg-Mueller and Raschka, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies have reported lower bone mineral density or bone mineral content in vegans compared with omnivores or other vegetarians (Chiu et al, 1997;Parsons et al, 1997;Outila et al, 2000). Another study found no difference in bone mineral density between vegans and lacto-vegetarians, although the researchers noted a positive correlation between calcium intake and bone mineral density (Lau et al, 1998). A small, short-term intervention study found that calcium balance remained positive after 10 days consuming a vegan diet as well as after 10 days consuming a lacto-vegetarian diet, despite a significantly lower mean calcium intake on the vegan diet (Kohlenberg-Mueller and Raschka, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies found no differences in bone health indices between lacto-ovo-vegetarians and omnivores (New, 2004). However, three out of four of the studies reported lower bone mineral density or bone mineral content in vegans (who consume no animal products) compared with omnivores or other vegetarians (Chiu et al, 1997;Parsons et al, 1997;Lau et al, 1998;Outila et al, 2000), leading one reviewer to conclude that vegans have lower bone mineral density than nonvegans (Smith, 2006). Several dietary factors known or thought to influence bone health, and possibly also fracture risk, including intakes of calcium, vitamin D, protein (including the ratio of plant to animal protein), potassium, sodium and fruit and vegetables are likely to differ between vegetarians and nonvegetarians and between vegetarians and vegans (New, 2004;Prentice, 2004).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a 5-year prospective study of changes in radial bone density of elderly white American women no differences were seen in bone loss rates between the lacto-ovo vegetarians and the omnivorous group (Reed et al 1994). Furthermore, in the most recently published studies, bone mass was found to be significantly lower in the vegetable-based dietary groups (Chiu et al 1997;Lau et al 1998), although it is likely that protein 'undernutrition' may account for some of these differences (Rizzoli et al 1998).…”
Section: Vegetarianism and Skeletal Healthmentioning
confidence: 99%
“…More recent studies with postmenopausal Asian women showed spine or hip BMD was significantly lower in long-term vegans (41,42). Those Asian women, who were vegetarian for religious reasons, had low intakes of protein and calcium.…”
Section: Bone Healthmentioning
confidence: 99%